Survey of Black Hole Attack Detection Techniques in Wireless Sensor Network - Chinthamani, R; Selvi, V (International Journal of Computer Sciences and Engineering, 2020)
Secure sending is a problematic task because of the partial nature of wireless sensor network properties. This paper provides solution to recognize malicious nodes in wireless sensor networks concluded prevention of black hole attack. It is basically a set of portable hosts associated wirelessly without slightly central management, where respectively node acts as a packet contributor, packet receiver, and a router at the same time. According to the landscape of this system, the active topology and the absence of a central management source some security problems and occurrences, such as the black hole attack, the wormhole attack, and the impression and negation attack. In this survey, we are going to introduce the Black Hole attack security issues and some of the recognition systems used to distinguish the black hole attack. In this kind of attack (black hole attack) the interlopers manipulate the normal performance of the network, by introduc0069ng themselves as the node with the shortest path to the destination. Interlopers can do a malicious behaviour over the network. Our future approach based on a new routing algorithm which educations shortest path in order to avoid malicious node path. Our results demonstrate the success and the effectiveness of our proposed routing procedure.